PENGARUH PENERAPAN LKS BERORIENTASI PEMBELAJARAN BERBASIS MASALAH TERHADAP KOMPETENSI SISWA KELAS X SMA NEGERI 1 GUNUNG TALANG - Yana Dirza Amalia (Universitas Negeri Padang, 2014)
LKS oriented Problem Based Learning is expected to optimize the activity and thinking patterns of students in learning process. Competencies which is achieved by students would be optimal if implemented learning contextual. One of the learning model that can optimize Physics student competence is Problem Based Learning. The purpose of research is to determine and investigate the effect of applying LKS oriented Problem Based Learning to competence of Physics student class X of SMAN 1 Gunung Talang. This research is quasi experimental research with Randomized Control Group Only. The research population are students of class X Science SMAN 1 Gunung Talang listed in the academic year 2013/2014. The sampling was Purposive Sampling technique. The research data includes the competence of three aspects those are cognitive, attitude, and skill. Data were analyzed by using two common test mean that the t test on knowledge and attitude aspects, whereas the t’ test was used for the skill aspect. Based on the analysis of the data can be presented two results of this research. First, the competence of students in learning physics using LKS oriented Problem Based Learning for aspects of knowledge, attitude aspects, and aspects of each skill 75.90, 81.50, and 76.67. Secondly, there are significant impact using LKS oriented Problem Based Learning on all aspects of competence grade X of SMAN 1 Gunung Talang on the real level of 0.05